Collaborative Supervision of Direct Cash Transfer-Village Fund in Tuban Regency - Denny Iswanto; Devi Maya Sofa; Dea Putri Aprilia (CV. Austronesia Akademika, 2024)
A number of social safety net programs have been provided to the community, one of which is through BLT-DD. BLT-DD is a new type of social assistance where the village government is given the authority to manage the technical implementation in each village by involving stakeholders to be able to implement this policy with full responsibility. This authority was given as the government's final step to be able to capture poor and vulnerable people who have not been touched by any social assistance, either from the central or regional government in Tuban Regency. In implementing the Village Fund BLT policy, it is necessary to have a monitoring system from upstream to downstream to ensure that the assistance provided is appropriate and on target. This research aims to determine participatory supervision in the implementation of BLT-DD in Tuban Regency. This research uses qualitative research methods with descriptive research type. Policy implementation is carried out by referring to government laws and regulations, both from Village Ministerial Decree No. 6 of 2020 to Tuban Regent's SE Number 140/2112 /414.106/2020 including activities for forming data collection teams, data collection mechanisms, setting targets, methods and mechanisms distribution, and monitoring and evaluation. In collaborative supervision, a coordination system has been implemented between the Inspectorate, PMD Service, Social Service and Village Government and BPD. This confirms the government's commitment to ensuring that social assistance is provided in an appropriate and targeted manner to poor and vulnerable communities at the village level.